POSTURAL STABILITY, PHYSICAL ACTIVITY, AEROBIC CAPACITY AND THEIR ASSOCIATIONS FOR YOUNG PEOPLE WITH AND WITHOUT INTELLECTUAL DISABILITIES - Blomqvist, Sven; Wester, Anita; Persson, Elin; Sundkvist, Hillevi; Sundelin, Gunnevi; Rehn, Börje (European Journal of Adapted Physical Activity, 2014)
Previous studies show that people with intellectual disability (ID) appear to have impaired postural stability,a lower level of physical activity, and lower aerobic capacity compared to persons without ID, limitationsthat could affect their health. This study investigates these physical functions and their associations in agroup of young people with ID compared to an age-matched group without ID. In total, this cross-sectionalstudy included 106 high school students (16-20 years): 57 students with mild to moderate ID and 49 agematchedstudents without ID (control group). Tests were performed for postural stability, level of physicalactivity, and aerobic capacity. Both females and males with ID had significantly lower estimated maximumoxygen uptake (l O2/min) (p< 0.001 for females and p=0.004 for males) and a lower aerobic capacityexpressed relative to body weight (ml O2/ kg*min) (p< 0.001 for females and p=0.012 for males) comparedto age-matched peers. Analyses of associations were made using the Pearson's correlation coefficient andmultivariate linear regression analysis. No significant associations could be found. Physical status appearsimpaired for young people with ID and functions, such as postural stability, should be evaluated separately.
Keywords: Mental retardation; physical capacity; motor activity; postural equilibrium; youth; teenagers